A Rare and Potentially Fatal Etiology of Hypercalcemia in an Infant. (5th August 2019) - Sonawalla, Ambreen; Tas, Vildan; Raisingani, Manish; Tas, Emir
Abstract : Hypercalcemia is an uncommon finding in children. Hypercalcemia has various etiologies including parathyroid dependent and independent mechanisms. Increased activity of the 1-alpha-hydroxylase enzyme in granulomatous diseases is a well-defined but an extremely rare cause of hypercalcemia in pediatric patients, particularly in infants. We describe the case of an infant who presented with failure to thrive, hepatosplenomegaly, and hypercalcemia who was initially treated with steroids but was later diagnosed with disseminated histoplasmosis in the absence of an underlying immunodeficiency. Extra caution should be used before considering steroids for the treatment of hypercalcemia and, whenever possible, steroids should not be initiated until a definite etiology is identified.